Предмет: Алгебра, автор: qweerty

Упростите выражение (b+1b-1 - bb+1):3b+12b-2

Ответы

Автор ответа: magickrai
0

1 действие:

b+1      b         (b+1)2 - b2-b        b2+2b-1-b2-b         b-1            1

___ - ____ = ______________ =  _____________ = ______   =  _____

b-1     b+1          (b+1)(b-1)            (b+1)(b-1)         (b+1)(b-1)  b+1

 

2действие:

 1       3b+1         1           2(b-1)        1          2(b-1)       2

__  : ______ =  _____  *  ______ = -  ___  *   ______  = _____

b+1    2b-2         b+1         3b+1          b-1        3b+1        3b+1

Похожие вопросы
Предмет: Математика, автор: juliaorehova2009